Nasal Symptoms Among Allergic Rhinitis Patients Could Contribute to Sexual Dysfunction - Zhang H; Zhang H; Jin P; Yu K; Zi X; Liang X; Zhang H; Zhao L (Journal of Asthma and Allergy, 2025)
Hailing Zhang,* Hongping Zhang,* Peng Jin, Kena Yu, Xiaoxue Zi, Xu Liang, HongYang Zhang, Li Zhao Department of Otolaryngology, The Second Hospital of Shandong University, Jinan, 250033, People’s Republic of China*These authors contributed equally to this workCorrespondence: Li Zhao, Department of Otolaryngology, The Second Hospital of Shandong University, Jinan , Shandong, 250033, People’s Republic of China, Email entzhaoli@126.comBackground:  Allergic rhinitis (AR) is a prevalent chronic inflammatory airway disease with a range of symptoms that can significantly impact quality of life. This study aimed to explore the relationship between the severity of nasal symptoms and sexual function in AR patients.Methods:  A case-control study involving 1034 AR patients and 422 healthy controls was conducted. Nasal symptoms were assessed using Visual Analog Scale (VAS) scores, while sexual function was evaluated using the International Index of Erectile Function (IIEF) for males and the Female Sexual Function Index (FSFI) for females.Results: In female AR patients, total FSFI scores, as well as scores for subjective arousal, orgasmic function, and intercourse satisfaction, were significantly decreased compared to controls. Nasal obstruction scores were significantly correlated with sexual desire, subjective arousal, orgasmic function, intercourse satisfaction, and total FSFI scores (r=− 0.3176, r=− 0.2106, r=− 0.6129, r=− 0.3430, r=− 0.5233). Dysosmia scores also correlated with subjective arousal, orgasmic function, intercourse satisfaction, and total FSFI scores (r=− 0.4331, r=− 0.3123, r=− 0.5259, r=− 0.5436). Overall disease severity correlated significantly with subjective arousal, orgasmic function, intercourse satisfaction and total scores (r=− 0.2908, r=− 0.3703, r=− 0.3739, r=− 0.4225). Among male AR patients, lower total IIEF scores were observed, with reductions in erectile function, sexual desire, and overall satisfaction. Nasal obstruction scores were negatively correlated with erectile function, orgasmic function, sexual desire, and total IIEF scores (r=− 0.8544, r=− 0.3869, r=− 0.2772, r=− 0.6855). Furthermore, rhinorrhea scores showed significant correlations with overall satisfaction and total IIEF scores (r=− 0.3711, r=− 0.2680), and dysosmia scores were significantly associated with erectile function, orgasmic function, sexual desire, and total IIEF scores (r=− 0.5048, r= − 0.2904, r=− 0.5607, r=− 0.4733). Overall disease severity correlated significantly with erectile function, orgasmic function, sexual desire and total scores (r=− 0.5385, r=− 0.2034, r=− 0.3257, r=− 0.4833).Conclusion:  This study underscores the negative correlations between nasal symptoms and sexual function in AR patients, suggesting that AR may contribute to sexual dysfunction.Keywords: allergic rhinitis, sexual function, nasal symptom, IIEF, FSFI